Flexural bond strength of natural hydraulic lime mortar and clay brick. - PAVIA, SARA (My University, 2010)
This paper measures the bond strength of natural hydraulic-lime (NHL) mortars, to further characterise their properties and enhance their use in building. An additional objective is to correlate bond strength with mortar hydraulicity, water content, workability and water retention, to develop mortars of high bond strength that would improve the quality of masonry. To this aim, the flexural bond strength of masonry, built with mortars of three hydraulic strengths-each including the water amount required to attain three specific flows (165, 185 and 195 mm), was measured with the bond wrench test. The results suggest that NHL mortars possess high water retention, and this enables a strong bond that compares well to that of Portland cement and cement/lime mortars. The results also indicate that bond strength is not determined by the binder?s hydraulic strength, but it increases proportionally to the mortar?s water retention. The paper concludes that for the NHL5 mortars, the 185 mm flow results in the strongest bond, simultaneously providing the highest water retention and best workability. However, for the lower strengths (NHL 2 and NHL 3.5 mortars), the water content required to attain the flows that provide an optimum workability (165 and 165?185 mm, respectively) does not lead to the strongest bond, but it is the highest flow values that provide the NHL2 and NHL3.5 mortars with the strongest bond and, in most instances, the highest water retention.
PUBLISHED
Keywords: Flexural bond strength; Natural hydraulic-lime mortar; Bond wrench test; Workability; Water retention; Initial flow